건강하던 12개월 여아에서 발생한 호중구감소증을 동반한 괴저성농창 1예와 문헌고찰 - 윤지수; 김동현; 이승주; 방현호; 배선미; 박경배; 이성열; 정기진; 최영진; 이현정; 박준수 (Allergy asthma & respiratory disease, 2018)
Ecthyma gangrenosum (EG) is a rare skin manifestation which starts with a maculopapular eruption and followed by a necrotic ulcer covered with black eschar. EG usually occurs in immunosuppressed patients with Pseudomonas aeruginosa sepsis. We present a previously healthy 12-month-old girl with EG by P. aeruginosa and agranulocytosis due to influenza A and then rhinovirus infection, without bacteremia. It is important for allergists to culture wound and differentiate EG from other skin disorders including Tsutsugamushi disease and initiate appropriate empiric antipseudomonal antibiotic treatment, and to evaluate for possible immunodeficiency, even in a healthy child. KCI Citation Count: 0